2021
DOI: 10.4239/wjd.v12.i9.1563
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and bariatric surgery in kidney transplantation: A clinical review

Abstract: Obesity is increasing worldwide, and this has major implications in the setting of kidney transplantation. Patients with obesity may have limited access to transplantation and increased posttransplant morbidity and mortality. Most transplant centers incorporate interventions aiming to target obesity in kidney transplant candidates, including dietary education and lifestyle modifications. For those failing nutritional restriction and medical therapy, the use of bariatric surgery may increase the transplant cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 89 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…Among all GLP-1RAs, liraglutide is the most commonly used with sufficient long-term data regarding its safety and efficacy. T2DM patients receiving liraglutide can lose 4–6 kg after 6–12 months of treatment [ 3 ]. Semaglutide may have a greater body weight–lowering effect than liraglutide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all GLP-1RAs, liraglutide is the most commonly used with sufficient long-term data regarding its safety and efficacy. T2DM patients receiving liraglutide can lose 4–6 kg after 6–12 months of treatment [ 3 ]. Semaglutide may have a greater body weight–lowering effect than liraglutide.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the dietary programs fail to obtain a persistent weight loss allowing those patients to receive a KT. In many cases, bariatric surgery is the only effective alternative, but is associated with surgical and metabolic complications [ 2 , 3 ]. The recent recommendations from the European Renal Association Working Group DESCARTES suggest that therapies such as glucagon-like peptide receptor agonists (GLP-1RAs) should be considered as an alternative therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same median weight loss was sustained throughout the entire follow-up time after KT and translated into a 26%TWL at 5 years after KT among eligible patients. While there is no consensus on the optimal timing (either before or after KT) and the ideal type of metabolic/bariatric surgery in patients with obesity and advanced CKD, it has repeatedly been shown that the improvement in obesity-related conditions and the significant weight loss after bariatric surgery not only increases access to transplant but also likely decreases the postoperative adverse events after KT and hence should ideally be offered prior to KT [ 20 , 27 ]. The importance of such sequence in approach is evident for patients with extreme obesity (BMI ≥ 60 kg/m 2 ) and so is the significance of a multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, many studies, systematic reviews and metanalyses have explored the role of BS on KTx [ 11 , 12 ]. Furthermore, it has to be highlighted that data regarding simultaneous robotic KTx and BS for patients with severe obesity and ESRD has been recently published [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the included studies were heterogeneous and thus, the power to draw firm conclusions was limited [ 11 ]. Another recently published clinical review points out the benefits of BS in KTx, but without any clear consensus regarding its optimal timing [ 12 ]. Little is known about how BS impacts the bioequivalence of tacrolimus currently available commercial products and immunosuppression pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%